Application in silico Modeling Simulation in Bioequivalence Studies: A Review - Sekar Ayu Pawestri (Journal of Food and Pharmaceutical Sciences, 2023)
Bioequivalence testing aims to ensure that the therapeutic performance of the drug is consistent and reproducible when it is administrated. Modeling and simulation in silico methods are currently performed to conduct virtual bioequivalence studies. Various computer simulation software is used to generate the simulation and model input data. This review summarizes the software used for predicting in vivo performance which supports the analysis of virtual bioequivalence testing. GastroPlus™ and SimCyp® are widely used platforms in generating data for virtual bioequivalence studies. The studies suggest that the validity procedure is necessary for modeling and simulation. The in silico method has become a valuable tool in bioequivalence studies as supporting extension of the biowaiver drug list and contributing to future drug development.